The Role of Family Support on Self-Care Behavior in Patients Diabetes Mellitus (DM) Type 2 - Mahardika Primadani; Surahma Asti Mulasari; Sunarti Sunarti (Lambung Mangkurat, 2022)
Diabetes Mellitus (DM) is a chronic disease as a metabolic disorder described by an increase in glucose levels above the average. 80% of the prevalence of DM, most of them are type 2 DM. Self-care is one of the important things that people with DM must do to prevent complications. The purpose of this study is to determine the role of family support on self-care behavior in patients with Type 2 DM. The method used is a full text critical review in English on the PubMed, Scopus, Web of science and Google Scholar databases with research subjects with type 2 DM. There are 7 articles that meet the inclusion criteria related to the topic. Analysis of 7 articles showed that family support could improve self-care behavior of patients with type 2 diabetes. Having family support will make type 2 DM sufferers have a higher level of adherence in controlling blood sugar.